2010
DOI: 10.1177/0193945910381597
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Correlates of Nutrition Among Migrant Farm-Worker Children

Abstract: Past research has demonstrated a higher incidence of overweight children in migrant farm-worker (MFW) families than in the general U.S. population. This study provided descriptive data on MFWs’ acculturation, household food security, and general self-efficacy, and children’s food patterns and body mass index. Convenience samples of 60 parent–child dyads were obtained from six MFW camps in two Midwest states. Acculturation and food security were low, higher general self-efficacy was associated with low accultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 46 publications
(71 reference statements)
0
42
1
Order By: Relevance
“…Compared with the general US population, this unique population shows wide-ranging deficits in education, literacy levels, fluency in English, and for our immediate concern, health status. 3 Children of migrant farmworkers are particularly vulnerable and show greater occurrence of obesity, while simultaneously experiencing insufficient culturally relevant health interventions in their communities and/or surroundings. 3,4 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the general US population, this unique population shows wide-ranging deficits in education, literacy levels, fluency in English, and for our immediate concern, health status. 3 Children of migrant farmworkers are particularly vulnerable and show greater occurrence of obesity, while simultaneously experiencing insufficient culturally relevant health interventions in their communities and/or surroundings. 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…3 Children of migrant farmworkers are particularly vulnerable and show greater occurrence of obesity, while simultaneously experiencing insufficient culturally relevant health interventions in their communities and/or surroundings. 3,4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research has shown that a paradigm exists with migrant families. These workers harvest produce to bring fresh fruits and vegetables to the tables of American families, and yet the children of migrant workers rarely meet the U.S. Department of Agriculture recommended minimum food group servings of fruit or vegetables; neither do they meet recommendations for grains, dairy, and meat (Kilanowski, 2012;Kilanowski & Moore, 2010). National surveys show that rates of unhealthy weight in Latino youth are higher than the majority population, but the Latino subpopulation of migrant farmworker children measure even higher (Kilanowski, 2010(Kilanowski, , 2012Ogden, Carroll, Kit, & Flegal, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Migrant parents who want to participate in health promotion interventions may not have the time after returning from the fields because they still need to wash, cook the evening meal, and attend to their children’s needs (Kilanowski, 2012). As for reimbursing participants for their time, gift cards may be given per institutional policy; however some remote areas may not have local stores that accept gift cards.…”
mentioning
confidence: 99%